Lucratividade de clientes: a utilização do custeio baseado em atividades e tempo sob enfoque do custo para servir aplicado numa empresa do setor alimentício - Alvares, Anderson (2011)
The knowledge of the customer profitability is important information to define specific policies and actions. The profitability analysis indicates the portion of profit that each customer contributes to the result of the company. Customers have different needs and therefore consume company resources differently. Measuring the Cost to Serve answers to the company how much it costs to serve each customer, distribution channel, region etc. The Activity Based Costing (ABC) came in the late 80s, with the aim of measuring the cost of products, customers and other costing objects with greater accuracy, thus avoiding distortions caused by the use of criteria for apportionment, based on volume, the allocation of indirect costs. However, even with the benefits provided by ABC, many companies withdrew their application in practice, pointing out several difficulties. Kaplan and Anderson (2004) presented as a solution to the difficulties encountered in using the ABC, Activity Based Costing and Time (TDABC), whose purpose is to simplify the costing process, using time as a major driver of costs. In that sense, this paper presents an exploratory case study with a single company in the food industry, located in São Paulo. We analyzed the 248 enterprise customers in order to verify if the TDABC can simplify the measurement of the cost of processing applications and provide relevant information to the analysis of customer profitability. The paper presents as the main objective the use and analysis of TDABC in measuring the cost of processing applications. In general, the study showed that TDABC can simplify the process of costing, however, care is needed to calculate the rate of capacity cost and the development of equations of time. Whereas the findings and results of this study were obtained from a single company, it is suggested to future researchers to apply the subject in companies in other sectors